The Role of Health Risk Communication in Improving Community Preparedness for Disasters - Ester (Miracle Journal Get Press, 2026)
The increasing frequency and complexity of disasters require strengthening community preparedness through effective health risk communication strategies. This study aims to analyze the role of health risk communication in improving community preparedness for disasters and examine risk perception as a mediating variable. This study used a quantitative approach with an explanatory design and a cross-sectional survey of 245 respondents in disaster-prone areas. Data were collected using a structured questionnaire based on the Health Belief Model (HBM) and Protection Motivation Theory (PMT), then analyzed using Structural Equation Modeling (SEM). The results showed that risk communication significantly influenced risk perception (β=0.62; p<0.001) and community preparedness (β=0.29; p<0.001). Risk perception also significantly influenced preparedness (β=0.48; p<0.001) and partially mediated the relationship between risk communication and preparedness (β indirect=0.30; p<0.001). The research model had a good fit and explained 56% of the variation in community preparedness. These findings confirm that clear, credible, timely, and participatory risk communication can enhance preparedness by shaping proportionate threat perceptions. This research contributes to the development of a community-based health risk communication model and offers practical implications for the formulation of more responsive and evidence-based disaster mitigation strategies in disaster-prone areas.